A POLYPHONIC THEORY OF ENUNCIATION IN LYRIC POETRY: THE CASE OF IVAN SLAMNIG (Philological Studies, 2019)
In this paper, interpretation problems in reading lyric poetry are presented and analyzed in the light of a polyphonic theory of enunciation by Oswald Ducrot, Lacanian psychoanalysis, and Antony Easthope's take on Marxist criticism. Taking sides with Marxist and psychoanalytic criticism, the author introduced arguments about what makes lyric poetry an autonomous discourse, the latter being primarily involved with presenting mechanisms that attempt to represent it. This idea is at odds with an understanding of lyric poetry as a private language of poet's soul and of the lyric subject as a narcissistic image of the poet/the reader. Lyric poetry of Ivan Slamnig holds a special place in contemporary Croatian lyric poetry inasmuch as it reveals the extent to which irony depends upon the polyphony of enunciation. This results in breaking the myth of originality of poetic language, while openly constructing a poetics through destructing of other poetics.
Keywords: a polyphonic theory of enunciation; psychoanalysis; Marxist criticism; poetry of Ivan Slamnig; irony